2019
DOI: 10.1101/537514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Ventromedial Prefrontal Cortex Disrupts Consolidation of Fear Memories

Abstract: Anxiety disorders pose one of the biggest threats to mental health worldwide, yet current therapeutics have been mostly ineffective due to issues with relapse, efficacy, and toxicit. Deep brain stimulation (DBS) is a promising therapy for treatment-resistant psychiatric disorders including anxiety, but very little is known about the effects of DBS on fear memories. In this study, we used a modified plus-maze discriminative and showed that DBS of the ventromedial prefrontal cortex (vmPFC) was able to disrupt co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 76 publications
6
27
0
Order By: Relevance
“…On the contrary, we found that dropout applied post training dramatically decreases the accuracy of prediction, which is similar to the disruption of memory seen when DBS was applied during consolidation of memory in our previous animal studies [6] (Fig 1D).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…On the contrary, we found that dropout applied post training dramatically decreases the accuracy of prediction, which is similar to the disruption of memory seen when DBS was applied during consolidation of memory in our previous animal studies [6] (Fig 1D).…”
Section: Discussionsupporting
confidence: 87%
“…To the best of our knowledge, this paper is the first to suggest a cohesive mechanism in which disruption of neural activity through DBS can lead to both disruption and enhancement of memory. Although no behavioural experiments were performed in conjunction with our modelling, we based the models on our previous animal behavioural experiments that showed memory enhancement with DBS prior to the behavioural task [8] and memory disruption with DBS dur-ing consolidation of memory [6], which demonstrated similar results to the present paper.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations